Association of Hypertension and Activity of Angiotensin Converting Enzyme in Malaria Patients Attending Sheik Muhammad Jidda General Hospital, Kano State, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Peptides of the renin angiotensin aldosterone system (RAAS) have been implicated in the pathogenesis of malaria infection; however, available data are limited. Thus, this study was aimed at determining the association between hypertension and activity of angiotensin converting enzyme (ACE) in malaria patients attending Sheikh Muhammad Jiddah General Hospital, Kano State, Nigeria.Materials and Methods:Four hundred and fifty consenting adults (300 malaria positive and 150 control participants) were evaluated. Data on sociodemographic characteristics were obtained using a questionnaire. ACE level was determined as described by Cushman and Cheung (1971) and blood pressure (BP) was evaluated using standard methods.Statistical Analysis:ACE activity and BP were expressed as mean ± SEM. Comparison between groups was carried out using one-way analysis of variance. Pearson’s Chi-square (χ2) test was employed to establish association betweenPlasmodiuminfection, hypertension, sex, age, educational, and occupational status.P